Columnar and equiaxed solidification in a microgravity environment ? The CETSOL project - MOONEY, ROBIN (My University, 2017)
The formation of the microstructure and the grain structure during solidification is affected by buoyancy-driven flow and movement of crystals growing in the melt. To allow for pure diffusive solidification conditions, i.e., suppressing melt flow and sedimentation and floatation effects, experiments in microgravity environment were performed in the frame of the ESA Map programme CETSOL (Columnar-to-Equiaxed Transition in SOLidification Processing). This contribution presents an overview of results obtained so far, focussing on 2 topics: First, to investigate the columnar-to-equiaxed transition (CET), refined and non-refined Al-7wt%Si alloys were solidified with different process parameters on-board the International Space Station ISS. From extensive analysis of the samples the microstructures and the grain structures were determined as well as critical parameters for CET. These results are compared to results obtained with different numerical models showing a fairly good agreement. Second, growth of equiaxed dendrites was investigated in-situ using the transparent model alloy Neopentylglycol-(d)Camphor in microgravity environment during the sounding rocket mission MASER-13. The growth of individual dendrites was directly observed with CCD cameras, providing information of the 3D shape of dendrites and of the dendrite morphology evolution.
6th Decennial International Conference on Solidification Processing, SP17
PUBLISHED
Old Windsor, UK
Keywords: columnar-to-equiaxed transition; equiaxed dendrite; microgravity; solidification; Nanoscience & Materials; ALLOYS; Columnar to equiaxed transition; Microgravity/Reduced Gravity Experiments; SOLIDIFICATION